Antineutrophil Cytoplasmic Antibody Induction due to Infection: A Patient with Infective Endocarditis and Chronic Hepatitis C - Fareed B. Kamar; T. Lee-Ann Hawkins (Canadian Journal of Infectious Diseases and Medical Microbiology)
While antineutrophil cytoplasmic antibody (ANCA) is often used as a diagnostic marker for certain vasculitides, ANCA induction in the setting of infection is much less common. In the case of infective endocarditis, patients may present with multisystem disturbances resembling an autoimmune process, cases that may be rendered even trickier to diagnose in the face of a positive ANCA. Though not always straightforward, distinguishing an infective from an inflammatory process is pivotal in order to guide appropriate therapy. We describe an encounter with a 43-year-old male with chronically untreated hepatitis C virus infection who featured ANCA positivity while hospitalized with acute bacterial endocarditis. His case serves as a reminder of two of the few infections known to uncommonly generate ANCA positivity. We also summarize previously reported cases of ANCA positivity in the context of endocarditis and hepatitis C infections.